The Relationship between Psychological Meaningfulness and Employee Engagement: Moderating Effect of Age and Gender - Ruslan, Ruswahida binti Ibnu; Islam, Md. Aminul; Noor, Idris Mohd (Journal of Asian Scientific Research, 2014)
There has been a great deal of interest in employee engagement over the years, and it has become a popular term. However, there is no one universally acceptable definition for employee engagement until now. Employee engagement has been defined in many ways, and its assessment also seems to be similar, as developed by scholars such as Kahn [1] who coins the term psychological meaningfulness. This paper reviews the literature surrounding employee engagement, especially in terms of psychological meaningfulness. Next, this paper observes existing theories of employee engagement. This paper also attempts to find out whether age and gender moderate the relationship between psychological meaningfulness and employee engagement. Review of existing literature confirms that psychological meaningfulness is an important factor in gauging employee engagement.